Cold War Southeast Asia - Ybiernas, Vicente Angel S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 29 No 1 (2014): The 2014 TWSC Writeshop)
Review of Cold War Southeast Asia edited by Malcolm H. Murfett (Singapore: Marshall Cavendish Editions)